HUBUNGAN ANTARA KESEPIAN DENGAN SELFIE-LIKING PADA MAHASISWA - Krisnawati, Evina; Soetjiningsih, Christiana Hari (Jurnal Psikologi, 2017)
This study aims to examine the relationship between loneliness and selfie-liking. The hypothesis of this research is that there is a positive relationship between loneliness and selfie-liking among college students. This research used correlational quantitative methods. Participants in this research was 64 students, which was taken by purposive sampling technique, with inclusive criteria: like to do selfie and in the last month post the selfie photos to social media as much as 4-6 times. Data were collected using the Loneliness Scale from UCLA Version 3 and selfie-liking measured by Selfie-Liking Scale.Â  The correlation was analyzed using the Spearman Correlation Test with SPSS 23 for Windows. The results showed there was a positive and significant relationship between loneliness and self-liking (r=.297; p=.009) which means the higher loneliness, the higher selfie-liking.